PROSES DEODORISASI DALAM REFINING MINYAK SAWIT: PENGARUH SUHU DAN TEKANAN VAKUM TERHADAP KADAR ASAM LEMAK BEBAS DAN KUALITAS WARNA - Veriska, Hanin Dita; Youfa, Rita (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
Deodorization is a crucial stage in palm oil refining aimed at removing components that cause odor and flavor, such as free fatty acids (FFA) and peroxides. This process utilizes high temperatures and vacuum pressure in a prestripper machine. The study evaluates the impact of temperature and vacuum pressure on the quality of the resulting oil. Findings indicate that the optimal temperature for deodorization is approximately 267°C with a vacuum pressure of 2.8 mbar, effectively reducing FFA levels below 0.1% and improving oil color. Excessive temperatures or inadequate vacuum pressure can increase FFA levels and darken the oil, thereby compromising product quality. Precise control of operational conditions during the deodorization process is essential for ensuring palm oil meets industry quality standards, reducing energy waste, and enhancing production efficiency. In conclusion, accurate regulation of temperature and vacuum pressure is vital for consistently producing high-quality oil.